2019
DOI: 10.1016/j.ymthe.2019.05.011
|View full text |Cite|
|
Sign up to set email alerts
|

circRNA_0025202 Regulates Tamoxifen Sensitivity and Tumor Progression via Regulating the miR-182-5p/FOXO3a Axis in Breast Cancer

Abstract: Tamoxifen is the most commonly used endocrine therapy for patients with hormone receptor (HR)-positive breast cancer. Despite its initial therapeutic efficacy, many patients eventually develop drug resistance, which remains a serious clinical challenge. To investigate roles of circular RNAs (circRNAs) in tamoxifen resistance, a tamoxifen-resistant MCF-7 cell line was established and screened for its circRNA expression profile by RNA sequencing. hsa_circ_0025202, a circRNA that was significantly downregulated, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
237
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 353 publications
(258 citation statements)
references
References 53 publications
8
237
0
Order By: Relevance
“…In addition, miR-378 expression declined, accompanied by remarkably increased expression of its target ornithine decarboxylase 1 (ODC1) from 0 to 18 h after PH [36], and ODC1 was found that involved in positive regulation of cell population proliferation [37]. Our results were consistent with those reports by others about the expression of ceRNAs was negatively correlated [38], showing that circ_03848 might target these miRNAs and affect downstream gene expression in regulating cell proliferation. Additionally, circ_08236 exhibited an upregulated pattern at 36 h after PH and predicted to target rno-miR-143-5p in this paper.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, miR-378 expression declined, accompanied by remarkably increased expression of its target ornithine decarboxylase 1 (ODC1) from 0 to 18 h after PH [36], and ODC1 was found that involved in positive regulation of cell population proliferation [37]. Our results were consistent with those reports by others about the expression of ceRNAs was negatively correlated [38], showing that circ_03848 might target these miRNAs and affect downstream gene expression in regulating cell proliferation. Additionally, circ_08236 exhibited an upregulated pattern at 36 h after PH and predicted to target rno-miR-143-5p in this paper.…”
Section: Discussionsupporting
confidence: 90%
“…Increasing study has indicated the vital role circRNAs play in tumor progression, and because of the relative tolerance of these circRNAs to exonuclease, it may be a better biomarker to judge the prognosis of patients [17]. Additionally, more and more circRNAs, for instance hsa_circ_0025202 [18], circAGFG1 [12], circGFRA1 [19], circ_ANKS1B [20], have been pointed out to play important roles in tumorigenesis, chemoresistance, apoptosis or metasta sis of BC. Nevertheless, many of the functions of circRNAs in BC remain to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, studies focused on the relationship between BC and circRNAs also achieved attention. For instance,circRNA_0025202 regulates tamoxifen sensitivity and tumor progression via regulating the miR-182-5p in Breast Cancer [31]. CircTADA2As suppress BC progression and metastasis via targeting miR-203a-3p [32].…”
Section: Discussionmentioning
confidence: 99%